2013
DOI: 10.1136/bmjopen-2013-003033
|View full text |Cite
|
Sign up to set email alerts
|

Shaping medicinal product information: a before and after study exploring physicians’ perspectives on the summary of product characteristics

Abstract: ObjectiveTo establish, in the context of the revised European Pharmacovigilance Directive and based on physicians’ perspectives, how Summaries of Product Characteristics (SmPCs) could be more user friendly and better support physicians’ interactions with patients, thereby improving patients’ own understanding of their medicines.DesignQualitative focus group discussions (step 1), development of an alternative SmPC (step 2) and an online quantitative survey (step 3) comparing the alternative SmPC to the currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…Clinical practice guidelines (CPGs) provide guidance to health care professionals on patient monitoring . CPGs thus aim to bridge the gap between clinical research and clinical practice and to aid health care professionals in evidence‐based decision making .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practice guidelines (CPGs) provide guidance to health care professionals on patient monitoring . CPGs thus aim to bridge the gap between clinical research and clinical practice and to aid health care professionals in evidence‐based decision making .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to health care professionals, the practical usefulness of the responses is important. As an example, a qualitative study of the German Summary of Product Characteristics (SPCs) concluded that physicians found them disorganised and difficult to use [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides the above mentioned regulatory requirements, there are scientific studies specifically done on the positive and negative aspects of using illustrations or other graphic elements in the MPIs and other written documents (e.g. bullets or headings) . Illustrations increase attention, comprehension and recall of health materials, this being particularly relevant for the low‐literate patients, and especially if pictures are associated with written text or oral instructions .…”
Section: Introductionmentioning
confidence: 99%
“…Given the current regulatory requirements and the existing body of literature, it was considered relevant to characterise the graphic elements in a representative sample of Portuguese MPIs, as well as to evaluate the level of potential users' comprehension regarding illustrations and tables from the sampled MPIs. In this context, two exploratory studies were developed (Study A and B): Study A aimed to a) characterise (quantitatively and qualitatively) all the following key graphical elements, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation